Accounting as an information base for the social policy implementation in the company’s management - Ometsinska, Iryna (Herald of Economics, 2019)
The article considers the economic essence of the concepts of social accounting, sociallyoriented accounting, and social activity. It is found that carrying out social activities requires incurring social costs, which are presumably understood as the reduction of economic benefits in the form of disposal of assets and increase in obligations related to the implementation of company’s social policy. These expenditures result in a decrease in equity (except for a reduction in capital due to its withdrawal or distribution by the owners) within the operational, financial or investment activities of the enterprise.It is stated that depending on the trends, social expenditures should be divided into: personnel costs (wages and salaries (basic, extra, financial rewards and compensation payments), labor protection and occupational safety, personnel training and development, maintaining company’s social facilities); customer costs (warranty service, product quality assurance); state and society costs (taxes, charity donations, regional development programs, support for sports and cultural activities); natural environment protection costs (environmental and ecological payments).The need to display information on social costs in management and financial reporting is confirmed. In this regard, it is proposed to use the management reporting form called “A Statement on Social Expenditures” and the form from section XVI named “Directions of social policies” of the Notes to the annual financial statements, whose items are arranged in four categories: personnel, environment; state and society; customers.It is pointed out that the publication of social reporting has certain advantages for enterprises (a higher credibility from special interest groups; better relations with the state; attracting investments; better business reputation; gaining a competitive advantage; making sound decisions in pursuing social policies) and for the state and society (encouraging socially responsible business; efficient use of resources; drawing attention to sustainable development; information transparency).The need for state regulation of social reporting in Ukraine is emphasized, and it is claimed that the lack of it brings into question reliability and validity of the information provided by enterprises in such reporting.